Simultaneous Quantitation of Clevidipine and Its Active Metabolite H152/81 in Human Whole Blood by LC-MS/MS: Application to Bioequivalence Study - Li, Pengfei; Wu, Haitang; Zhao, Zhixia; Du, Ping; Xu, Haitong; Liu, Hongchuan; Zhou, Yu; Yu, Weiyue; Li, Hao; Liu, Lihong (Frontiers in Chemistry, 2022)
Clevidipine is an ultrashort-acting dihydropyridine calcium antagonist, which can control blood pressure accurately. It is necessary to develop a liquid chromatography–tandem mass spectrometry (LC-MS/MS) method to quantitate clevidipine and its active metabolite H152/81 for clinical pharmacokinetic study and therapeutic drug monitoring. Liquid–liquid extraction was used for sample preparation, and clevidipine-d7 and H152/81-13C-d3 were chosen as the isotope internal standard. The chromatographic separation was performed on an ACE Excel 2 Phenyl column (50 × 2.1 mm). Mass quantification was carried out on the multiple reaction monitoring of the transitions of m/z 473.1→338.1, 480.1→338.1, 356.0→324.0, and 362.2→326.2 for clevidipine, clevidipine-d7, H152/81, and H152/81-13C-d3. The validated method gave an excellent linearity over a concentration range of 0.1–30 ng/ml for clevidipine and 2–600 ng/ml for H152/81. Other fully validated content such as accuracy, precision, extraction recovery, matrix effect, and stability were also investigated and showed satisfactory results. It was strongly recommended that whole blood is the first choice for clinical bioanalysis. Using whole blood for sample analysis can reduce the whole blood collection volume (1 ml vs. 4 ml) and shorten the time from sample collection to storage to 5 min, and there is no centrifugation process and precooling in the ice water bath, which can further reduce the instability caused by exposure. The method was successfully applied to a bioequivalence study of clevidipine butyrate-injectable emulsion.